Information technology in banking and entrepreneurship - Toni Ahnert; Sebastian Dörr; Nicola Pierri; Yannick Timmer (European Central Bank (ECB), 2024)
We study the importance of information technology (IT) in banking for entrepreneurship. Guided by a parsimonious model, we establish that job creation by young firms is stronger in US counties more exposed to banks with greater IT adoption. We present evidence consistent with banks' IT adoption spurring entrepreneurship through a collateral channel: entrepreneurship increases by more in IT-exposed counties when house prices rise. Further analysis suggests that IT improves banks' ability to determine collateral values, in particular when collateral appraisal is more complex. IT also reduces the time and cost of disbursing collateralized loans.
Keywords: D82; G21; L26; 330; technology in banking; entrepreneurship; information technology; collateral; screening